2010
DOI: 10.3155/1047-3289.60.10.1204
|View full text |Cite
|
Sign up to set email alerts
|

Updating the Conceptual Model for Fine Particle Mass Emissions from Combustion Systems Allen L. Robinson

Abstract: Atmospheric transformations determine the contribution of emissions from combustion systems to fine particulate matter (PM) mass. For example, combustion systems emit vapors that condense onto existing particles or form new particles as the emissions are cooled and diluted. Upon entering the atmosphere, emissions are exposed to atmospheric oxidants and sunlight, which causes them to evolve chemically and physically, generating secondary PM. This review discusses these transformations, focusing on organic PM. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 77 publications
2
144
0
Order By: Relevance
“…After emissions are diluted to ambient concentrations (evaporating semivolatile compounds), OH exposure results in large increases in aerosol mass and oxygen content (23). However the aging mechanism driving this enhancement is uncertain.…”
mentioning
confidence: 99%
“…After emissions are diluted to ambient concentrations (evaporating semivolatile compounds), OH exposure results in large increases in aerosol mass and oxygen content (23). However the aging mechanism driving this enhancement is uncertain.…”
mentioning
confidence: 99%
“…where DR t [1] and DR t [2] are determined by eq 1 and eq 3, respectively. The values were less than 7.4%, which indicated that the DR t determined by two ways were comparable.…”
Section: Resultsmentioning
confidence: 99%
“…18 Robinson et al reviewed recent developments in the understanding of contribution of emissions from combustion process to fine PM mass, focusing on organic aerosols and updated the conceptual model for fine particle mass emissions from combustion systems. 1 A recent review paper by Maricq and Maldonado summaries the spirit of two Coordinating Research Council PM Measurement workshops and one of the consensus is that dilution sampling can provide comparable results in laboratory and real-world applications. 20 The bulkiness of early dilution samplers was a major barrier to their widespread application for field source test.…”
Section: àmentioning
confidence: 99%
See 2 more Smart Citations